PENGARUH PENGAWASAN DAN PEMBERIAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN PADA HOTEL RESTY MENARA PEKANBARU - Johan Brenly Situmorang; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The research was conducted at the Resty Hotel Menara Pekanbaru while the purpose of this study was to determine the effect of supervision and motivation on employee job satisfaction at the Resty Menara Pekanbaru hotel. Supervision and Giving Motivation as an independent variable (X1X2) while Job satisfaction is the dependent variable (Y). In this study the method used was quantitative descriptive with the SPSS program. The population in this study were all employees of Resty Menara Pekanbaru Hotel, amounting to 58 people. Samples taken based on census method, where the population is sampled is 58 respondents. Data collection method using questionnaire method, testing the hypothesis using multiple linear regression analysis with the results of the study that is Y = 13.997 + 0.503X1 + 0.359X2.Research that has been carried out shows the results that response response to the influence of supervision, giving motivation, and employee job satisfaction at Hotel Resty Menara Pekanbaru in the Agree category. Whereas for the t test that has been done shows that the variables of supervision and giving motivation partially have a significant effect on employee job satisfaction. And F test results show that simultaneously shows that the variables of supervision and giving motivation have a significant effect on employee job satisfaction. And the calculation of the coefficient of determination (R2) obtained adjusted R square value of 0.713, this indicates that the influence of supervision variables and giving motivation to employee job satisfaction is 71.3%. While the remaining 28.7% is influenced by other variables not included in this study.Keywords: Supervision, Motivation, and Job Satisfaction